EFEKTIVITAS PROGRAM PENANGGULANGAN PENGANGGURAN KARANG TARUNA "EKA TARUNA BHAKTI" DESA SUMERTA KELOD KECAMATAN DENPASAR TIMUR KOTA DENPASAR - Budiani, Ni Wayan (INPUT Jurnal Ekonomi dan Sosial, 2009)
Unemployment Prevention Program of Karang Taruna “Eka Taruna Bhakti” is a program that held by Karang Taruna Eka Taruna Bhakti in South Sumerta that aimed to prevented unemployment problems in South Sumerta and also to develop prosperity of the society in South Sumerta. This program held since 2005. The events that include in this program are kinds of training for the manpower corporate with government departments or private foundations. Beside that, there is also a distribution of menpowers to the componies in South Sumerta. This research is aimed to analyzed the effectivity of unemployment prevention program that held by Karang Taruna Eka Taruna Bhakti in South Sumerta which is located in East Denpasar, where this research is useful for organizer of the unemployment program, in order those problems and weakness can be prevented so that those do not bother the running of the program in the future. The effectivity level of unemployment prevention program is measured through the goals of accuracy, socialization of the program, knowledge of the responden about the objective of the program, and the monitoring program by Karang Taruna officer.